Dropping out aspects of indigenous university students in Colombia (2016)
Despite Colombian law and human rights state basic rights must be guaranteed to all citizens (no matter their racial condition is), it is shown that population like indigenous minorities still have difficulties to access higher education and in the same way, the ones that reach university, also face circumstances which force them to drop out. On the other hand, it is important not to ignore the fact that Colombian government’s institutions in charge of watch over citizens’ education and guarantee indigenous populations’ rights are partially involved in this process. Real testimonies of these people reveal that even when university quotas are recently given to these communities, students’ guidance is missing so they can achieve not only get to university but, finish studies successfully. This paper intends to analyze the current situation of indigenous people accessing higher education and at the same time, to evaluate the Colombian government’s role when the must offer education guarantees and development to indigenous minorities without affect their culture identity.